2013
DOI: 10.1186/1471-2342-13-25
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of primary Sarcomas of the great vessels in CT, MRI and PET/CT: a single-center experience

Abstract: BackgroundTo investigate the imaging features of primary sarcomas of the great vessels in CT, MRI and 18 F-FDG PET/CT.MethodsThirteen patients with a primary sarcoma of the great vessels were retrospectively evaluated. All available images studies including F-18 FDG PET(/CT) (n = 4), MDCT (n = 12) and MRI (n = 6) were evaluated and indicative image features of this rare tumor entity were identified.ResultsThe median interval between the first imaging study and the final diagnosis was 11 weeks (0–12 weeks). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Thus, it is important to make an effort to detect intravascular masses through imaging studies. Recently, the advantages of MRI for diagnosing AIS have been reported by von Falck et al who demonstrated that a pedunculated or lobulated appearance and subtle enhancement during first-pass perfusion were consistent with AIS (18). Regrettably, Gd-enhanced MRI, which was performed in our patient, did not focus upon the origins of the renal arteries, which could have detected the primary lesion at the right renal artery bifurcation area.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, it is important to make an effort to detect intravascular masses through imaging studies. Recently, the advantages of MRI for diagnosing AIS have been reported by von Falck et al who demonstrated that a pedunculated or lobulated appearance and subtle enhancement during first-pass perfusion were consistent with AIS (18). Regrettably, Gd-enhanced MRI, which was performed in our patient, did not focus upon the origins of the renal arteries, which could have detected the primary lesion at the right renal artery bifurcation area.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, FDG-PET/enhanced CT or MRI-DWIBS failed to yield findings indicative of AIS. The FDG uptake has been reported to be poor in intimal sarcomas (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intimal sarcoma of the pulmonary artery was reported to have a prevalence of 0.001% based on autopsy findings (6). Generally, a lesion of the pulmonary intimal sarcoma is localized to a single pulmonary artery, as in this case (7). FDG-PET scanning shows an increased uptake of FDG to the intimal sarcoma lesions in most cases (2).…”
Section: Discussionmentioning
confidence: 94%
“…The degree of FDG uptake tends to be significantly higher in the latter group. 6,7 The mainstay of therapy for these tumors is surgical resection, which may prolong tumor-free survival. 7,8 The role of chemotherapy is unclear, and there are no consensus recommendations for specific therapeutic regimens.…”
mentioning
confidence: 99%